Rules of Speech Behavior in Tatar and Turkish Proverbs - Edikhanov, Iskander Zhamilovich; Nabiullina, Guzel Amirovna; Latypov, Renat Islamgarayevich; Karahan, Akarturk (International Journal of Criminology and Sociology, 2022)
Today, despite the abundant supply and scientific papers concerning particular features of multi-method, communicative culture and comparative linguistic research on the ethnocultural stereotypes of Turkic peoples' communicative behavior, it is vital in modern linguistics. The issue statement is because the ethnocultural examination of the Turkic peoples' communicative behavior permits us to look at the ethnos' communicative culture in the modern context and distinguish typical and distinctive characteristics of the Tatar's communicative culture Turkish peoples. This survey investigates the ethnocultural stereotypes of the communicative behavior of the Tatar and Turkish linguistic cultures expressed in the paroemiological fund. The analysis is based on the Tatar and Turkish languages' phraseological and paroemiological units within this article's framework. The research adopted descriptive, stylistic, and comparative techniques. Moreover, The methodological framework is the linguoculturological, cognitive-linguistic aspects of the investigation of paroemiological units. The most substantial typical categories of the Tatars' communicative culture are the culture of communication, politeness, sociability, verbiage, silence, conflict communication, and effective communication. In paroemias, truth is proclaimed before lie, laconicalness before loquacity, silence before speaking, deed before the word, listening before speaking. The examination of stereotypes of communicative behavior reveals that the Tatars persist faithfully to the observance of folk traditions and particular speech cultures.